Targeting T-bet expressing B cells for therapeutic interventions in autoimmunity - Sachinidis, Athanasios; Lamprinou, Malamatenia; Dimitroulas, Theodoros; Garyfallos, Alexandros (Clinical and experimental immunology, 2024)
Summary Apart from serving as a Th1 lineage commitment regulator, transcription factor T-bet is also expressed in other immune cell types and thus orchestrates their functions. In case of B cells, more specifically, T-bet is responsible for their isotype switching to specific IgG sub-classes (IgG2a/c in mice and IgG1/3 in humans). In various autoimmune disorders, such as systemic lupus erythematosus and/or rheumatoid arthritis, subsets of T-bet expressing B cells, known as age-associated B cells (CD19+CD11c+CD21−T-bet+) and/or double-negative B cells (CD19+IgD−CD27−T-bet+), display an expansion and seem to drive disease pathogenesis. According to data, mostly derived from mice models of autoimmunity, the targeting of these specific B-cell populations is capable of ameliorating the general health status of the autoimmune subjects. Here, in this review article, we present a variety of therapeutic approaches for both mice and humans, suffering from an autoimmune disease, and we discuss the effects of each approach on T-bet+ B cells. In general, we highlight the importance of specifically targeting T-bet+ B cells for therapeutic interventions in autoimmunity. Targeting of ABCs/DN, in mice models of autoimmunity and/or humans suffering from autoimmune disorders, leads to diminished levels of T-bet expression in B cells and thus improves the general health status of the subjects. Graphical Abstract Graphical Abstract